Mechanisms of Regulated and Dysregulated CARD11 Signaling in Adaptive Immunity and Disease - Bedsaul, Jacquelyn R.; Carter, Nicole M.; Deibel, Katelynn E.; Hutcherson, Shelby M.; Jones, Tyler A.; Wang, Zhaoquan; Yang, Chao; Yang, Yong-Kang; Pomerantz, Joel L. (Frontiers in Immunology, 2018)
CARD11 functions as a key signaling scaffold that controls antigen-induced lymphocyte activation during the adaptive immune response. Somatic mutations in CARD11 are frequently found in Non-Hodgkin lymphoma, and at least three classes of germline CARD11 mutations have been described as the basis for primary immunodeficiency. In this review, we summarize our current understanding of how CARD11 signals, how its activity is regulated, and how mutations bypass normal regulation to cause disease.